2007
DOI: 10.1002/marc.200600790
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Mode Microwave‐Assisted Atom Transfer Radical Polymerization Catalyzed by [RuCl2(p‐cymene)(PCy3)]

Abstract: In the atom transfer radical polymerization (ATRP) of methyl methacrylate in the presence of [RuCl2(p‐cymene)(PCy3)] (p‐cymene = 4‐isopropyltoluene, PCy3 = tricyclohexylphosphine), a microwave effect is noted which strikingly depends on both the temperature and the method used (conventional microwave synthesis (CMS, i.e., without simultaneous cooling) or enhanced microwave synthesis (EMS, with simultaneous cooling)). Thus, between 85 and 120 °C under CMS conditions, microwave‐assisted polymerizations take plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 83 publications
0
27
0
Order By: Relevance
“…The benzene ring occupies one face of octahedron, and a tridentae ligand among L1 and L3-L6 the opposite one. In the cation of 1 the Ru-S(1) bond distance, 2.3921 (19) Å , is greater than its Ru-S(2) distance, 2.3465 (19) The Ru-Se bond distances of [(η 5 -C 5 Me 5 )Ru(μ 2 -SeR) 3 (η 5 -C 5 Me 5 )Ru]Cl (R=tolyl) (2.446(4)-2.466(4) Å ) 54 are shorter than those of cations of 2 and 5, because RSe -is expected to be bonded strongly in comparison to selenated Schiff bases and their reduced analogues. In [Ru(MeCp)(PPh 3 )] 2 (μ-Se 2 ) 2 (Otf) 2 , Ru-Se bond distances are 2.518(1) and 2.556(1) Å , 55 somewhat longer than those of cations of 2 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…The benzene ring occupies one face of octahedron, and a tridentae ligand among L1 and L3-L6 the opposite one. In the cation of 1 the Ru-S(1) bond distance, 2.3921 (19) Å , is greater than its Ru-S(2) distance, 2.3465 (19) The Ru-Se bond distances of [(η 5 -C 5 Me 5 )Ru(μ 2 -SeR) 3 (η 5 -C 5 Me 5 )Ru]Cl (R=tolyl) (2.446(4)-2.466(4) Å ) 54 are shorter than those of cations of 2 and 5, because RSe -is expected to be bonded strongly in comparison to selenated Schiff bases and their reduced analogues. In [Ru(MeCp)(PPh 3 )] 2 (μ-Se 2 ) 2 (Otf) 2 , Ru-Se bond distances are 2.518(1) and 2.556(1) Å , 55 somewhat longer than those of cations of 2 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…CMS (conventional microwave synthesis) and EMS (enhanced microwave synthesis) for ATRP of methyl methacrylate. [11] Poly(diallyldimethylammonium chloride), PDADMAC, is a cyclic polycation, which has been widely used in many industrial and biological applications, for example as flocculent in wastewater treatment, antimicrobial biocide and biocatalyst agents in biological, medical, food applications and layer-by-layer assembly. [12,13] The kinetics and mechanism of homo-and copolymer syntheses, chemical structures, polyelectrolyte behavior in solution, molecular characterization and interactions in solution and at interfaces has been reviewed by Hunkeler et al [14] The use of conventional free radical polymerization is able to provide homopolymers or random copolymers of DAD-MAC but this method has its limitation in providing more complex macromolecular architectures that allow for finely controlled property modification.…”
Section: Communicationmentioning
confidence: 99%
“…Calc. for C 14 The solution (in 5 mL water) of Na 2 [PdCl 4 ] (0.294 g, 1 mmol) was mixed with a solution of L 1 (0.288 g, 1 mmol) or L 2 (0.367 g, 1 mmol) made in acetone (10 mL …”
Section: Synthesis Of Lmentioning
confidence: 99%
“…The compounds, [Ru@C@C@CR 2 (L)(Cl)(arene)][PF 6 ] (L = PCy 3, PPr i 3 ), are reported as excellent catalyst precursors for ring closing olefin metathesis by Dixneuf's group [13]. The atom transfer radical polymerization of methyl methacrylate has been catalyzed with [RuCl 2 (g 6 -p-cymene)(PCy 3 )] [14]. Dixneuf and his co-workers have reported that in situ generated catalyst, from [RuCl 2 (g 6 -p-cymene)] 2 and a pyrimidinium or benzimidazolium salt in the presence of Cs 2 CO 3 , selectively promotes the diarylation of 2-pyridylbenzene with arylbromides [15].…”
Section: Introductionmentioning
confidence: 99%